Nuansa Fiqh Sosial KH. MA. Sahal Mahfudh - Ahmad Faisal (Al-Ulum, 2010)
Most religious studies (read: how to conduct the fiqh) is dominated by the tendency of theory-centric. As a result, in the social context, the doctrine contained in the fiqhhas not often been seen in the direction of the practical forms of life. Therefore, in accordance with the nature and process of ijtihad, changes the perspective ofjurisprudence; hence, it becomes more realistic and dynamic, is possible and necessary. Thus, fiqh can be optimized and actualized as the values and behavior insocial life which continues to develop. According to the cleric Mahfud, there have to be spirit to change the paradigm of the paradigm on how to do the fiqh from "truthorthodoxy" towards paradigm of "social meaning," If the first deals with reality on truth and the character fiqh is "black and white" in facing the reality, the seconduses jurisprudence as a "counter discourses" and demonstrates a meaningful character.